Stalin - von der Revolution zur Supermacht - Kaminski, Hartmut (Germany : Sonstige Studios, 2003)
This documentary follows the incredible political evolution of Stalin from the 1917 Bolshevik revolution until the moment when he became the absolute ruler over the Soviet Union and former Eastern Europe. His political career and his regime are recreated with the help of Dmitri Volkogonov, former general in the Red Army, author of one of the many biographies of Stalin published in the past decades. The documentary is highly dependent on Volkogonov's historiographical approach on Stalin's biography. The documentary also contains a large collage of archival footage. It is split into four episodes, according to some of the phases of either Stalin's activity or of his regime: Stalin's youth and the revolution, the collectivization and the first Five Year Plan, the Great Purges, and the Second World War with its aftermath of USSR becoming a Superpower and Stalin reaching the peak of his might and tyranny.
Duration: 03:32:00